Dissociative and sympathomimetic toxicity associated with recreational use of 1-(3-trifluoromethylphenyl) piperazine (TFMPP) and 1-benzylpiperzine (BZP) - Wood, David M. (Springer-Verlag, 2008)
INTRODUCTION: There is emerging evidence of increasing use of legally available synthetic compounds as recreational drugs. While there are some changes to legislation relating to these synthetic compounds, often the emergence of the agents outpaces the effect of the legislation to curb their use, and the legal status of these agents may change as more information on their toxicity becomes known. TFMPP [1-(3-trifluoromethylphenyl) piperazine] was initially temporarily controlled under Schedule I of the Controlled Substances Act in 2002 in the US, but following further review and lack of published information on toxicity, it was removed from this control in 2004. In addition, there are very few “user reports” of effects when TFMPP is taken alone or in combination with BZP [1-benzylpiperazine]. CASE REPORTS: Three patients presented to our emergency department after ingesting 4 tablets thought to be 3,4-methylenedioxy-N-methylamphetamine (MDMA, street name “Ecstasy”) over the course of an evening. They presented with dissociative-type symptoms, nausea, and signs consistent with sympathomimetic toxicity. All 3 improved with conservative management and observation, within 12 hours of presentation. Serum analysis demonstrated the presence of TFMPP and BZP at concentrations of 263 ± 5.8 ng/mL (range 260–270 ng/mL) and 46.7 ± 15.3 ng/mL (range 30–60 ng/mL), respectively. No other recreational drugs were detected in an extended toxicological screen of blood and urine samples. DISCUSSION: This is the first case series of confirmed toxicity associated with recreational use of TFMPP in combination with BZP, with clinical features not consistent with BZP toxicity. In our view, the current legal status of TFMPP should be reviewed.